Integer-valued self-exciting periodic threshold autoregressive processes - Pereira, Isabel (2016)
In this paper, the periodic self-exciting threshold integer-valued autoregressive model of order one with period $T$ driven by a periodic sequence of independent Poisson-distributed random variables is introduced and analyzed in detail. Basic probabilistic and statistical properties of the model are discussed as well as parameter estimation and forecasting.